Seasonal Variation in Physico-chemical Parameters of Groundwater in Yerraguntla Area of YSR Kadapa DT, Andhra Pradesh, India - Suresh Pulapaka (Chemistry and Biochemistry: Research Progress Vol. 1, 2025)
People around the globe are in tremendous trouble because of unexpected changes in the physical, chemical, and natural states of the air, water, and soil. Due to the increased mortal population, industrialization, use of diseases, and man-made exertion, water is heavily contaminated with different dangerous pollutants. Disposing of contaminated jewels, filtering soils, and mining processing lead to contamination of natural water. The quality of drinking water must be checked regularly. Because of this contaminated drinking water, the mortal population suffers from varied forms of waterborne diseases. The vacuity of good quality water is a necessary point for precluding the conditions and perfecting the quality of life. It is necessary to know the details about different Physicochemical parameters such as Hydrogen ion concentration, Electrical Conductivity, Total Dissolved Solids, Total Hardness, Calcium, Magnesium, Sodium, Potassium, Bicarbonate, Chloride, Sulphate, Phosphate, Dissolved Oxygen, Biochemical Oxygen Demand, Chemical Oxygen Demand, etc. for testing water quality. Yerraguntla area of YSR Kadapa district was selected to determine the groundwater quality in both rainy and summer seasons. In the present study, the results showed that most of the Physico-chemical parameters exceeded the admissible limits of WHO. The water Quality Index showed that groundwater is not suitable for drinking purposes in all locales of the study area. The correlation measure showed the inter-relevance between various parameters that impact groundwater quality. Piper tri direct illustration showed that the groundwater of the area contains Ca-HCO3 type of mariners. So, it is necessary to adopt sound water sanitation methods in the study area.